COMPUTER VISUALIZATION IN ECOLOGICAL EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The idea to use computer visualization in ecological education is promoted. A fragment of the virtual ecological trip “Lake Pryazhinskoe” is demonstrated. The approach to create virtual trips is based on Web-design technologies. The virtual ecological trips will open new innovative and creative possibilities for ecological education both at the stage of their development and their application.